Three-dimensional carbon- and binder-free nickel nanowire arrays as a high-performance and low-cost anode for direct hydrogen peroxide fuel cell - Ye, Ke; Guo, Fen; Gao, Yinyi; Zhang, Dongming; Cheng, Kui; Zhang, Wenping; Wang, Guiling; Cao, Dianxue (Journal of power sources, 2015)
A novel three-dimensional carbon- and binder-free nickel nanowire arrays (Ni NAs) electrode is successfully fabricated by a facile galvanostatic electrodeposition method using polycarbonate membrane as the template. The Ni NAs electrode achieves a oxidation current density (divided by the electroactive surface areas of Ni) of 25.1 mA cm−2 in 4 mol L−1 KOH and 0.9 mol L−1 H2O2 at 0.2 V (vs. Ag/AgCl) accompanied with a desirable stability, which is significantly higher than the catalytic activity of H2O2 electro-oxidation achieved previously with precious metals as catalysts. The impressive electrocatalytic performance is largely attributed to the superior 3D open structure and high electronic conductivity, which ensures the high utilization of Ni surfaces and makes the electrode have higher electrochemical activity. The apparent activation energy of H2O2 electro-oxidation on the Ni NAs catalyst is 13.59 kJ mol−1. A direct peroxide–peroxide fuel cell using the Ni NAs as anode exhibits a peak power density of 48.7 mW cm−2 at 20 °C. The electrode displays a great promise as the anode of direct peroxide–peroxide fuel cell due to its low cost, high activity and stability. [Display omitted] •The Ni NAs shows unique 3D open nanowire arrays structure with a large surface area.•The Ni NAs exhibits superior catalytic activity and stability for H2O2 oxidation.•The DPPFC with Ni NAs anode displays a peak power density of 48.7 mW cm−2 at 20 °C.